Development of Crystal Guava Chips Home Industry as Typical Souvenir Products of Tanjung Anom Village - Juliana Nasution; Agiet Mutiara Rengganis; Maisaroh Maisaroh; Muhammad Fathoni (Penerbit Jurnal Indonesia, 2023)
The development of small and micro enterprises (SMEs) in indonesia is one of the priorities in national economic development. This is because the business is the backbone of the people’s economic system which is not only aimed at reducing the problem of inequality between income and between business actors, or to alleviate proverty and create jobs. Home industry is one the business units/companies on a small scale which is engaged in a certain industry. This business is usually produced by associations of housewives. The role of the home industry is very meaningful in empowering the community to have independence in the economic field. Tanjung Anom Village, Pancur Batu District, Deli Serdang Regency has an extensive guava cultivation farm, this is an alternative opportunity for community economic development. This research was conducted with a qualitative descriptive method. The data collected is based on the results of interviews, observations, and documentation from the place and the relevant sources. From the results of the study, it can be concluded that qualitatively business actors gain additional knowledge, understanding, and insight as well as basic skills about online product marketing.